Cerebral vascular shunting and oxygen metabolism in sickle cell disease - Alexander K. Song; Wesley T. Richerson; Megan A. Aumann; Spencer L. Waddle; R. Sky Jones; Samantha Davis; Lauren Milner; Chelsea Custer; L. Taylor Davis; Sumit Pruthi; Dann Martin; Lori C. Jordan; et al. (Blood Advances)
Abstract: Patients with sickle cell disease (SCD) are at elevated risk of silent cerebral infarcts and strokes; however, they frequently lack established stroke risk factors (eg, macrovascular arterial steno-occlusion) and the mechanisms underlying such events are incompletely characterized. This study evaluated cerebral hemometabolism with respect to imaging markers of vascular shunting in 143 participants with SCD, including 73 pediatric (aged 6-17 years) and 70 adult (aged 18-40 years) participants using 3-Tesla brain magnetic resonance imaging (MRI). Vascular shunting was assessed in each patient using a previously published ordinal venous hyperintensity score (VHS) of 0, 1, or 2 on cerebral blood flow-weighted MRI. Participants with VHS of 2, indicative of the most rapid arteriovenous transit, had significantly reduced blood oxygen content (CaO2; 10.90 ± 1.69 mL O2/100 mL blood), oxygen extraction fraction (OEF; 33.52% ± 5.54%), and cerebral metabolic rate of oxygen consumption (CMRO2; 2.91 ± 0.69 mL O2/100 g tissue per minute) compared with their counterparts with VHS = 0 (CaO2 = 12.42 ± 1.58 mL O2/100 mL blood; OEF = 39.03% ± 3.80%; CMRO2 = 3.77 ± 0.84 mL O2/100 g tissue per minute) or VHS = 1 (CaO2 = 11.86 ± 1.73 mL O2/100 mL blood; OEF = 36.37% ± 5.11%; CMRO2 = 3.59 ± 0.78 mL O2/100 g tissue per minute). Both pediatric and adult patients with SCD presenting with greater imaging evidence of vascular shunting had mildly reduced OEF and CMRO2. These findings highlight that imaging markers of vascular shunting are associated with significant, albeit mild, evidence of reduced OEF and CMRO2 in patients with SCD.